2020
DOI: 10.1155/2020/2915628
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of High Fertility Status among Women of Reproductive Age in Wonago District, Gedeo Zone, Southern Ethiopia: A Community-Based Cross-Sectional Study

Abstract: Background. High fertility remains one of the most important public health issues hampering the health and welfare of mothers and the survival of their children in developing nations. In Ethiopia, the high fertility rate has been seen for a long historical period with some pocket areas of high fertility still showing poor improvement. Hence, this study was aimed at determining the magnitude of high fertility status (number of children ever born alive≥5) and associated factors among women of the reproductive ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 21 publications
4
15
1
Order By: Relevance
“…The hospital is currently serving more than 100,000 peoples, and annually 400 mothers were delivered. The fertility rate in this study area was 69.1% [ 25 ]. The common language spoken in this study area was Amharic and Gedeoffa.…”
Section: Methodsmentioning
confidence: 99%
“…The hospital is currently serving more than 100,000 peoples, and annually 400 mothers were delivered. The fertility rate in this study area was 69.1% [ 25 ]. The common language spoken in this study area was Amharic and Gedeoffa.…”
Section: Methodsmentioning
confidence: 99%
“…However, over half of the non-first birth remains to occur within 3 years of their prior birth ( 6 ). In contrast, although, the county has shown remarkable changes in fertility reduction over the past two decades ( 23 ), fertility remained high, especially in the pastoralist area where fertility is too high, with a total fertility rate of above six per woman ( 6 , 24 , 25 ). Consistent with high fertility, the majority of births in Ethiopia (62%) fall into one of the high-risk categories.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to a community-based study conducted in Gedeo Zone (69.1%) and Tigray Region, Ethiopia (51%). 25 29 This figure was quite higher than the prevalence reported by other investigators ranging from 9.4% to 27% in Gambian, Cameroon, Nigeria, Tanzania and India. 2 33 34 41 42 The fact that later studies were all carried out in health facilities and urban catchment areas could explain these low prevalence rates.…”
Section: Discussionmentioning
confidence: 52%
“…A possible explanation is that women residing in the urban area stay longer in school, thereby postponing the time for marital engagement. 25 On the other hand, researchers found that education is an important factor for high parity, with several causal relationships from a theoretical perspective. 47 To sum up, education generally results in an improvement in the status of individuals in society in the form of a better understanding of health issues and employment status.…”
Section: Discussionmentioning
confidence: 99%